Pengaruh Ekstrak Bawang Putih (Allium Sativum) Terhadap Kadar Glukosa Darah Dan Gambaran Histopatologi Pankreas Pada Tikus Putih (Rattus Norvegicus) Galur Sprague-Dawley Yang Diinduksi Streptozotocin - Cyntithia, L. Gita; Windarti, Indri; Soleha, Tri Umiana (CV. Jasa Sukses Abadi, 2024)
Diabetes mellitus (DM) is one of the highest causes of death in the world whose prevalence increases every year, DM is characterized by elevated blood glucose levels and damage of the pancreas. Streptozotocin is a drug used to induce diabetes mellitus in experimental animals, single high dose administration can cause type 1 DM. Garlic has various component that have the potential as antidiabetic, anti-inflammatory and antioxidant. This study aim to determine the effect of garlic extract (Allium sativum) on blood glucose levels and pancreas histopathological images in white rats (Rattus norvegicus) Sprague-Dawley strain induced by streptozotocin. This research is an experimental study with a post test only control group design. This study used 24 rats and divided into 4 group, K- (normal group), K+ (STZ 60 mg/kgBB), P1 (STZ + garlic extract 500 mg/kgbb), P2 (STZ + garlic extract 750mg/kgBB). Blood glucose levels were assessed with a glucometer and the histopathological images of the pancreas was assessed by counting the number and size of the langerhans islet. The mean blood glucose levels for each group were K- = 73.3mg/dL, K+ = 400 mg/dL, P1=203.8 mg/dL, and P2=132.3 mg/dL. One Way ANOVA test obtained p value = 0.000. The mean number of langerhans islet in 10 fields of view obtained K- = 26.1; K+ = 4.6; P1= 7.8; P2=15.1. One Way ANOVA test obtained p = 0.000. The mean area of ​​the langerhans islet in each group obtained K- = 19092.4 µm2; K+ = 4759.3 µm2; P1=8561,4 µm2; P2=9621.8 µm2. Kruskal-Wallis test obtained p = 0.000 (p <0.05). There is an effect of garlic extract (Allium sativum) on blood glucose levels and pancreas histopathological images in white rats (Rattus norvegicus) Sprague-Dawley strain induced by streptozotocin.